A STUDY TO ASSESS THE CLINICAL AND BIOCHEMICAL PROFILE OF PATIENTS DIAGNOSED WITH HEPATITIS E IN A LARGE TEACHING HOSPITAL OF SOUTHERN INDIA - Chakrabarti, Keya; Ballala, Kirthinath; Rao N, Karthik; Patil, Navin; A, Avinash; Ahmed, Talha; Varghese, George; Kunder, Sushil Kiran (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Objective: Hepatitis E has been identified as a major health problem in developing countries and recently developed countries. To study the profile of patients diagnosed with hepatitis E infection in a tertiary care hospital in south India. Methods: A cross-sectional record-based study with the records of patients diagnosed with hepatitis E infection over a 40-month period from a teaching hospital in southern India and fulfilling the following criteria was performed. Results: The cases were predominant in the age group of 21-30 years with relative sparing of children. No seasonal variation in the occurrence or secondary cases was observed. Temporary derangement of liver function tests was recorded in all cases. The study showed a male preponderance. As documented in previous studies, the disease proved fatal in a primigravida who developed fulminant hepatic failure. Another interesting feature was the presence of leptospirosis, scrub typhus, and hepatitis A as co-infection with hepatitis E. Conclusion: In India, the awareness of the disease is also low, therefore, the diagnosis is usually not made in the majority of cases. Hence, the availability of data regarding the clinical pattern of presentation and biochemical profile is restricted. However, there are some questions still unanswered like the preference of the virus to infect individuals in the age group of 20-40 years, sparing of children, and increased rate of infection among the males. The cause of the increased morbidity and mortality of this virus in pregnant women is still not known. A larger sample size and the data on the seroprevalence of this disease in the population under study are necessary for a meaningful interpretation of its epidemiological pattern. Keywords: Alanine transaminase, Alkaline phosphatase, Aspartate aminotransferase, Bilirubin, Liver.